Bank efficiency and shareholder value in Vietnam Banking - Dang, Buu Kiem; Vo, Duc Toan (Economic Journal of Emerging Markets, 2025)
Purpose — This paper investigates the impact of bank efficiency on shareholder value in the context of Vietnamese commercial banks.Methods — Bank technical efficiency is measured using the DEA input cost minimization method. We employ fixed effects model (FEM), random effects model (REM), and two-step difference generalized method of moments (GMM) to regress the research models.Findings — The findings indicate that bank efficiency positively impacts shareholder value. Additionally, the study reveals that specific bank characteristics, such as return on equity, bank size, market risk, liquidity risk, and macroeconomic factors, such as GDP growth rate, inflation rate, and credit to the private sector, also affect shareholder value. Implications — We recommend that bank managers implement policies to enhance technical efficiency, creating greater shareholder value.Originality — This study is the first to explore the role of technical efficiency in predicting shareholder value, specifically within the context of Vietnamese banks.